Intellectual disability secondary to a 16p13 duplication in a 1;16 translocation. Extended phenotype in a four‐generation family. (25th November 2014) - Mohamed, Amal Mahmoud; Kamel, Alaa; Mahmoud, Wael; Abdelraouf, Ehab; Meguid, Nagwa
<x xml:space="preserve">Abstract</x> We describe a large family from the Gaza Strip presented with multiple congenital anomalies. The proband was presented with intellectual disability and multiple congenital anomalies including cleft palate, low‐set ears, everted upper lip, diaphragmatic hernia, and arthrogryposis. Pedigree analysis showed 19 affected patients over five generations, only 6 were alive and 11 individuals were obligate carriers. The proband had an apparently normal karyotype, although FISH studies showed a derivative chromosome 1 with duplication of 16p13.3 and deletion of the 1p subtelomere. Her father however had a balanced translocation. The seven affected patients had a similar phenotype, one of them died before genetic testing was carried out and the living six patients had the same unbalanced translocation. Array CGH revealed an 8.8 Mb duplication in 16p13 and 200, 338 bp deletion in 1p36.3. Accordingly, intellectual disability, hypertelorism, cupped ears, everted upper lip, and limb anomalies were presenting clinical features of the 16p13 duplication syndrome while deep set eyes were perhaps related to the 1p terminal deletion. Prevention of recurrent intellectual disability in this family can be achieved through carrier detection and prenatal genetic diagnosis. © 2014 Wiley Periodicals, Inc.